The interrelation between the Interpersonal, Representational and Morphosyntactic Levels for the expression of the volitive modality in Pope Francis' speeches - Oliveira, Andre Silva; Pessoa Prata, Nadja Paulino; Gasparini-Bastos, Sandra Denise [UNESP] (Univ Caxias Sul, Graduate Program Literature Culture & Regions, 2020)
This paper proposes to investigate, in the light of the theoretical assumptions of the Functional Discourse Grammar (FDG), the interrelation between the Interpersonal, Representational and Morphosyntactic Levels for the introduction of the volitive modality, based on the discourses of Pope Francisco that were made in the Spanish language. For this, we propose to describe and analyze the volitive modality based on the position of the Speaker in relation to the enunciator constructed in the discourse, the type of illocution, the modal values of the volition, the source and the target of the modal attitude and the forms of linguistics expression.
Keywords: Functional Discourse Grammar; Grammatical Component; Volitive Modality; Spanish language